2010
DOI: 10.1088/1367-2630/12/7/073006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the intrinsic ferroelectric polarization in orthorhombic HoMnO3

Abstract: Whether large ferroelectric polarization P exists in the orthorhombic HoMnO 3 with the E-type antiferromagnetic spin ordering or not remains as one of unresolved, challenging issues in the physics of multiferroics. The issue is closely linked to an intriguing experimental difficulty for determining P of polycrystalline specimens that conventional pyroelectric current measurements performed after a poling procedure under high dc electric fields are subject to large errors due to the problems caused by leakage c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 36 publications
3
42
1
5
Order By: Relevance
“…2 (b)). These dielectric properties of the strained o-HMO film are different from any of the reported bulk results [16][17][18] but are close to those of o-REMnO3 with smaller RE ions such as Tm 36 and Lu. 37 The 200 nm film exhibited different dielectric properties compared to the strained 20 nm film, as shown in Fig.…”
contrasting
confidence: 87%
“…2 (b)). These dielectric properties of the strained o-HMO film are different from any of the reported bulk results [16][17][18] but are close to those of o-REMnO3 with smaller RE ions such as Tm 36 and Lu. 37 The 200 nm film exhibited different dielectric properties compared to the strained 20 nm film, as shown in Fig.…”
contrasting
confidence: 87%
“…In Ref. 21 we also observed that the P r values were almost the same even after annealing in the O 2 atmosphere. Therefore, we conclude that the P r values as obtained from the hysteresis loops measured by the PUND method are not sensitive to the leakage level of the specimen, thus indicating that the PUND method provides the intrinsic electric polarization of the specimen.…”
Section: Resultsmentioning
confidence: 52%
“…The onset temperatures of ferroelectric polarization were found to be 26, 35, 37, and 38 K for R = Ho, Tm, Yb, and Lu, respectively, and they are consistent with the reported lock-in transition temperature, T L , in each compound. 17,21,22 It is noteworthy that all the hysteresis loops appearing in Figs. 3 and 4 show saturating behavior at high electric fields except in very low temperature regions below ∼10-15 K. Related to this observation, the coercive electric fields at temperatures above 15 K seem clearly lower than the maximum applied electric field in all the compounds.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations